Fluency Protocol Validation and Norms for Adults and Older People Among the Portuguese Population - Barradas, Ana Catarina Amaral (2022)
Fluency Tasks are commonly used in neuropsychological assessment due to their briefness, easiness of administration, independency from special equipment, and their sensitivity to cognitive decline resulting from serious clinical conditions. These tests allow the access to information regarding several cognitive domains, namely language, executive functions, processing speed, lexical retrieval, verbal production, and semantic memory. The Fluency protocol was administered to 195 cognitively healthy adults and older adults residents in the community, who were stratified according to various sociodemographic variables with a distribution similar to that observed in the Portuguese population. This study aimed to analyze the influence of sociodemographic variables on the participant's performance and establish normative data for the Portuguese population. Education level contributed significantly to the prediction of the Fluency scores. Thus, the normative data for the Portuguese population were established considering the strata levels of education included in this study.